Lands and tenants in South India : a study of Nellore District, 1850-1990 - Atchi Reddy, M. (Oxford University Press, 1996)
This book questions the accepted wisdom regarding the relative bargaining powers of landlords and tenants. With the help of unpublished data from the 1850s onwards, Atchi Reddy shows how tenancy has helped in a slow but smooth transfer of land from absentee landlords to tenants and other cultivators, often giving them an upper hand.